Lived Experiences of Parents Supporting the Education of Children from Vulnerable Families - Arlyn S. Gonzaga; Aida C. Abad (RIRAI Publisher, 2026)
Parental support plays a critical role in children's educational participation and success, particularly among families experiencing social, economic, and cultural vulnerabilities. This study explored the lived experiences of parents supporting the education of children from vulnerable families within the contemporary schooling context. Guided by a narratological qualitative design, the research examined parents' understandings of educational success, the influence of their life histories and social positioning on educational aspirations, the challenges encountered in supporting schooling, and the strategies employed to navigate these challenges. Data were collected through semi-structured interviews with 15 parent-participants selected using maximum variation purposive sampling and were analyzed through narratological thematic analysis. The findings revealed four interconnected themes. First, parents conceptualized educational success as holistic development encompassing school continuity, literacy, character formation, responsibility, future security, and cultural identity rather than academic achievement alone. Second, parental aspirations were shaped by personal experiences of poverty, interrupted schooling, migration, family responsibilities, and limited access to resources. Third, parents encountered multidimensional challenges, including financial constraints, emotional strain, time limitations, communication barriers, and cultural adjustment difficulties that affected their capacity to support their children’s schooling. Fourth, despite these challenges, parents demonstrated resilience through sacrifice, resourcefulness, family and community support networks, communication with teachers, faith, and hope. The narratives highlighted that parental support extends beyond material provision and includes emotional, moral, cultural, and relational dimensions.